Pulmonary hypertension and insulin resistance: a mechanistic overview - Zanotto, Tamires M.; Gonçalves, Any Elisa de Souza Schmidt; Saad, Mario J. A. (Frontiers in Endocrinology, 2024)
Pulmonary arterial hypertension (PAH) is a vascular remodeling disease, characterized by increased blood pressure levels in pulmonary circulation, leading to a restriction in the circulation flow and heart failure. Although the emergence of new PAH therapies has increased survival rates, this disease still has a high mortality and patients that receive diagnosis die within a few years. The pathogenesis of PAH involves multiple pathways, with a complex interaction of local and distant cytokines, hormones, growth factors, and transcription factors, leading to an inflammation that changes the vascular anatomy in PAH patients. These abnormalities involve more than just the lungs, but also other organs, and between these affected organs there are different metabolic dysfunctions implied. Recently, several publications demonstrated in PAH patients a disturbance in glucose metabolism, demonstrated by higher levels of glucose, insulin, and lipids in those patients. It is possible that a common molecular mechanism can have a significant role in this connection. In this regard, this narrative review intends to focus on the recent papers that mainly discuss the molecular determinants between insulin resistance (IR) associated PAH, which included obesity subclinical inflammation induced IR, PPAR gamma and Adiponectin, BMPR2, mitochondrial dysfunction and endoplasmic reticulum stress. Therefore, the following review will summarize some of the existing data for IR associated PAH, focusing on the better understanding of PAH molecular mechanisms, for the development of new translational therapies.